Thermal Performance Curves Reveal Alternative Energy Pathways at Stressful Temperatures: A Multi-Trait Analysis of Phenotypic Plasticity in Thalassiosira Pseudonana - Baker, K.G.; Doblin, M.A.; Robinson, Charlotte (TAYLOR & FRANCIS LTD, 2015)
Temperature drives algal function at levels of organisation from molecules to ecosystems. Understanding the underlying mechanisms influencing function will enable better prediction of responses to contemporary environmental change. Thermal performance curves (TPCs) quantitatively describe the relationship between biological rate processes (e.g. growth) and temperature. There has been a renewed interest in TPCs because of their success in predicting population or species-specific responses and the potential incorporation of empirical temperature-dependent relationships into mechanistic models. For the first time, we present a multi-trait analysis of thermal sensitivity in the cosmopolitan diatom Thalassiosira pseudonana and demonstrate the activation of alternative energy allocation under sub/supra optimal temperatures. T. pseudonana was exposed to a range of temperatures between 11 and 34°C where multiple traits describing fitness and biogeochemical function were measured. The optimum temperature for growth (TO) was ~20 °C (0.8 d-1) when cell size was smallest and the functional cross-section for light capture was largest (ϬPSII), ensuring more efficient light harvesting. Photochemical electron transport through PSII (ETRPSII) appeared to be greatest at the temperature extremes with rates of 0.0050 and 0.0055 mol electrons (mg Chlorophyll-a m-3)-1 at 11 and 35 °C, respectively. Surprisingly, unlike at the TO this energy (ETRPSII) did not appear to be utilised by carbon fixation or growth and may be indicative of alternative pathways. Under heat stress (35 °C), energy was redirected towards cell maintenance/repair as cell biomass remained stable for 3 days before cell death. Comparatively when subjected to cold stress (11 °C), cell wall silicification was greatest with potential implications for cell sinking rates. This study suggests that TPCs should be incorporated into contemporary evolution experiments, to explore adaptation mechanisms to understand constraints on how phytoplankton will respond to long-term ocean change.Discover the world's research.